Improving nerve and muscle function: an exploration of targeted nerve function replacement following differential delay periods in a rat model - Chunxiao Tang; Yuanheng Li; Xinxian Fan; Jiamei Guo; Yifeng Lin; Yifan Gao; Lin Yang (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Targeted Muscle Reinnervation (TMR) improves real-time control of EMG-based prostheses by connecting severed nerves to adjacent muscles, creating new EMG signals. However, TMR requires cutting original nerve connections, which can cause denervation atrophy and limit functional recovery. As an alternative, Targeted Nerve Function Replacement (TNFR) offers a fundamentally different approach by establishing a direct end-to-end anastomosis between an intact donor nerve and the original nerve of a target muscle, preserving existing neural pathways while providing supplementary neural input. This study evaluates TNFR efficacy in restoring denervated muscle function across different postoperative intervals in a rat model. Methods Thirty Sprague–Dawley rats (220–250 g) were divided into five equal groups (n = 6 per group): control (no transection), denervated (transection without repair), immediate TNFR after median nerve transection, 2-week delayed TNFR, and 4-week delayed TNFR. The median nerve was selected for reinnervation with the musculocutaneous nerve innervating the brachialis muscle serving as the anastomosis target. All assessments were conducted 4 weeks post-TNFR intervention, including intramuscular bipolar EMG recordings (1024 Hz sampling rate), behavioral assessment, muscle tension measurement, dorsal root ganglia (DRG) histology, and spinal cord motor neuron evaluation. Results Immediate TNFR significantly outperformed delayed interventions across all parameters. EMG amplitude and root mean square values were significantly higher in the immediate group (P < 0.05). Maximum contraction and tetanic contraction forces of biceps brachii showed superior recovery with immediate TNFR (P < 0.05). Histological examination revealed greater preservation of DRG sensory neurons following TNFR (P < 0.05). Immunofluorescence showed better preservation of synaptic protein expression in spinal cord motor neurons with immediate intervention. Immediate TNFR also prevented autophagic behavior seen in delayed intervention groups, suggesting improved neuropathic pain prevention. Conclusion Timing critically influences TNFR outcomes, with immediate intervention yielding optimal restoration of both motor and sensory functions. This study provides valuable insights for optimizing surgical strategies in peripheral nerve injury, with important implications for limb reconstruction, rehabilitation protocols, and prosthetic development. Graphical abstract